Stories Alberta Social Studies Teachers Tell: Influences of Christianity, Liberalism, and Secularism - Patrick, Margaretta (Alberta Journal of Educational Research, 2022)
This article examines how cultural and historical narratives influence the stories Alberta teachers tell about religion in their secondary social studies classrooms. The stories reveal the degree to which teachers are both thoughtful practitioners and shaped by their society. Study participants reflected this tension as the majority took religion seriously in all its complexity but also inadvertently re-inscribed secular liberal assumptions about religion that ultimately narrowed the stories. Particular attention is paid to teachers’ definitions of religion, including its relationship with conflict, and the connections among religion, citizenship, and multiculturalism. Definitions are crucial, and when unexamined, they impact the stories teachers tell. Keywords: Religion, Secularism, Citizenship, Liberalism, Religion Education Cet article examine l’influence des récits culturels et historiques sur les histoires que racontent les enseignants albertains sur la religion dans leurs classes d'études sociales secondaires. Ces récits révèlent à quel point les enseignants sont à la fois des praticiens réfléchis et façonnés par leur société. Les participants à l'étude reflètent cette tension, car la majorité d'entre eux prennent la religion au sérieux dans toute sa complexité, mais réinscrivent aussi par inadvertance des hypothèses libérales séculaires sur la religion qui finissent par restreindre les récits. Nous accordons une attention particulière aux définitions de la religion par les enseignants, y compris sa relation avec les conflits, et aux liens entre religion, citoyenneté et multiculturalisme. Les définitions sont cruciales, et lorsqu'elles ne sont pas examinées, elles ont un impact sur les histoires que racontent les enseignants. Mots clés : religion, laïcité, citoyenneté, libéralisme, éducation religieuse